Manajemen Pembinaan Akhlak Peserta Didik di Madrasah Aliyah (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine in depth the management of students’ moral development in Madrasah Aliyah as a strategic effort to cultivate character grounded in Islamic values. The background of this study is based on the phenomenon of moral degradation among students, as indicated by declining discipline, weak responsibility, reduced respect for teachers, and the emergence of various deviant behaviors influenced by technological advancements and social change. This research employs a qualitative approach with a literature review design, drawing on academic books, scholarly journal articles, and other relevant documents. Data collection was conducted through a systematic literature search, while data analysis utilized content analysis techniques to identify patterns, concepts, and relationships among ideas. The findings reveal that moral development must be positioned as the core of the educational process and integrated into all aspects of madrasa activities, including formal instruction, teacher exemplification, habituation practices, extracurricular programs, and school culture. The moral problems faced by students are multidimensional and require comprehensive and sustainable approaches. Therefore, the management of moral development in Madrasah Aliyah should be systematically designed through well-structured planning, implementation, and evaluation, as well as supported by synergy among the madrasa, family, and community. In conclusion, moral development is expected to produce students who are not only academically competent but also possess strong moral and spiritual integrity. Keywords: educational management, moral development, students, Madrasah Aliyah, Islamic education